Oral History System for Memory Management (OHS3M) / Ahmad Fuzi Md Ajis … [et al.] - Md Ajis, Ahmad Fuzi; Md Jali, Jafalizan; Idrus, Marlia; Timan, Hazila (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Dark data refers to information that exists within an organization but remains unanalyzed, unstructured, or inaccessible. While many cultural heritage were under its way of preservation through oral history, there were limited means of managing the existence of untapped oral history data and remain dark within the repository of oral history collection custodian. In this project, a platform to manage the preservation of oral history collection prototype has been developed known as Oral History System for Memory Management (OHS3M). This OHS3M will serve as a centralized platform to streamline the oral history documentation process, resulting in better organization and search capabilities. OHS3M will empower researchers, historians and stakeholders by providing a user-friendly interface for easy exploration, analysis and collaboration. It aims to leverage big data analytics to unlock the hidden potential of dark data within oral history collections. project on leveraging dark data from oral history collections represents a significant endeavor with far-reaching implications. By harnessing the power of big data analytics, this project has the potential to transform the way we explore, interpret, and learn from our historical heritage. It paves the way for a more inclusive and comprehensive understanding of our past, shaping a brighter future informed by the lessons learned from the voices of the past.